Formação da Rede Urbana do Sertão de Piranhas e Piancó da Capitania da Paraíba Setecentista - Soares, Maria Simone Morais (2012)
This dissertation investigates the formation of the urban network in the Hinterland of Piranhas and Piancó throughout the eighteenth century. The urban network is understood from the urbanizing policy implemented by colonial agents, the State, the Church and the economic agents, that sparked the occurrence of fixed points (villages to indoctrinate the natives, barracks, villages, towns and cities) and communication routes, linked to the flows generated by the expansion process of cattle ranching. The main objective is to check how was the structure of this urban network in the Hinterland of Piranhas and Piancó in the eighteenth century, through the activities of colonization agents. This is a research of historical synthesis that adopted, as the main procedure, an analysis of historiography and written documentation and cartographic on the issue. Was concluded that the formation of an urban network, in Hinterland of Piranhas and Piancó, occurred in the first half of the eighteenth century, linked to the process of War of the Barbarians", resulting in barracks and in villages to indoctrinate the natives; and, in the second half of the eighteenth century, marked by post-war, was implemented a policy of forming villages, initially established in Pombal's Period (1750 - 1777) and conducted to the rest of the century. In parallel, throughout the eighteenth century, was verified a formation of chapels for the installation of settlements, as a result of the interests of landowners in their local setting, through donations of land assets, which gave the initial apparatus for its existence. It is intended to contribute to the study of eighteenth-century urban history of Paraíba from these findings.